Aneurysm of a. gastroduodenalis as a source of gastric hemorrhage - A. I. Sukhodolia; S.A. Sukhodolia; O. V. Gryshchuk; V. P. Mosiichuk; V. D. Tokarchuk (Клінічна хірургія)
Aneurysm of a. gastroduodenalis as a source of gastric hemorrhage